18Th Century Vistula River Geography in View of Franciszek Florian Czaki’s Maps - Strzelecki, Krzysztof (Quaestiones Geographicae, 2013)
Old maps are proven to be very useful when it comes to solution of the modern research problems and are widely used in various science disciplines connected with specification of mutual relations between elements of the geographical environment. This fact stems from the increased consciousness of unique information recorded on old maps, which at their time constituted a basis for subsequent cartographical studies. The geographical characteristics of the Vistula river were depicted in a handwritten 12-sheet map made the first half of the 18th century by Franciszek Florian Czaki, a military cartographer. On the basis of his own terrain mapping, Franciszek Florian Czaki succeeded in creation of his work, which was intended to provide an example for the designed, detailed map of Poland, ordered by Józef Aleksander Jabłonowski, the Nowogród voivode, and later by the king Stanisław August Poniatowski. The map was fully based on terrain mapping, which included such details as: settlement, road and water networks, forests, land relief as well as main types of ownership: crown-, church-, and nobility-owned.